2017
DOI: 10.1371/journal.pone.0183092
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the King-Devick test in the assessment of concussed patients in the subacute and later stages after injury

Abstract: Although the King-Devick (K-D) test has been used frequently in assessing sports related concussion early after injury, its characteristics over time after injury and in patients with prolonged persistent symptoms are unknown. The purpose of this paper was to: evaluate the ability of the K-D Test to distinguish patients seen early after concussion from those with symptoms persisting more than 3 months compared to controls, assess changes in the K-D test times over time after concussion, and determine the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…The DEM test has demonstrated its use in developmental-age applications, compared to King Devick which has been used in stroke, sport, and concussion. [65][66][67] Nevertheless, since research and application cannot be limited, these differences in clinical use have become less significant, 22,68 and DEM and KD could coexist in the same field of application.…”
Section: Final Remarksmentioning
confidence: 99%
“…The DEM test has demonstrated its use in developmental-age applications, compared to King Devick which has been used in stroke, sport, and concussion. [65][66][67] Nevertheless, since research and application cannot be limited, these differences in clinical use have become less significant, 22,68 and DEM and KD could coexist in the same field of application.…”
Section: Final Remarksmentioning
confidence: 99%
“…Relatively few studies have evaluated the K-D test in an outpatient clinical setting. Subotic et al [24] assessed the diagnostic value of the K-D test in a cross-sectional comparison among acutely concussed patients, persistent post-concussive syndrome (PPCS) patients, and in healthy controls. PPCS patients took longer than healthy controls to complete the K-D test but participants with PPCS did not differ from acutely concussed patients and no differences were found between acutely concussed patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…PPCS patients took longer than healthy controls to complete the K-D test but participants with PPCS did not differ from acutely concussed patients and no differences were found between acutely concussed patients and controls. The authors concluded that the K-D test has more assessment value immediately following a concussive hit on the sideline and was most useful when athletes had pre-injury baseline scores [24]. Unfortunately, baseline K-D test scores are not available for every athlete.…”
Section: Introductionmentioning
confidence: 99%
“…The association between serum SNTF elevations and the lasting effects of mTBI on cognitive performance is complex, with many tests failing to uncover any significant prognostic relationship. This issue is complicated by the well-established influences of subject intelligence level and degree of education on performance of a number of cognitive tests (39)(40)(41)(42)(43)(44)(45)(46)(61)(62)(63)(64)(65)(66)(67). When applying tests in which performance varies widely across cases independently of mTBI, it can be challenging to discern the long-lasting effects of the injury itself.…”
Section: Discussionmentioning
confidence: 99%